Investigating the efficacy of graywater use at the household level - Alkhatib, Ramadan Y., author; Roesner, Larry A., advisor (Colorado State University. Libraries, 2008)
The use of graywater at the household level is gaining increasing popularity in both the United States and elsewhere. The treatment methods in the market are either too simple or too complicated for a household resident to use. Also, the effects of using graywater in landscape irrigation and the fate of chemicals in graywater are still unclear. The socio-economic aspects of graywater are variable from one place to another and need to be investigated in order to predict whether graywater use will be accepted or not by the people.

This study investigates the use of graywater at the household level. Three areas were investigated: (1) Graywater treatment at the household level, (2) Effects of using graywater in landscape irrigation, (3) Social response of the people in the Gaza Strip, Palestine.

A house was retrofitted with dual plumbing system to collect graywater. Several treatment schemes were evaluated. The schemes were: I) storage only, II) storage with aeration, III) storage with aeration followed by 24-hour settling, IV) storage with aeration followed by 24-hour settling, coarse filtration, and UV disinfection, V) storage with aeration followed by 24-hour settling, coarse filtration, 5-micron filtration, and UV disinfection, VI) point-of-use treatment using coarse filter and UV disinfection, VII) point-of-use treatment using coarse filter, UV disinfection, and 5-micron filter. The combination of aeration and settling achieved significant reductions in turbidity, COD, and BOD5 with efficiencies of 83% and 66% for COD and BOD5 respectively. Significant reductions in levels of indicator organisms were not achieved till after the introduction of UV unit in scheme IV. As a result, 3-log removal was achieved in the case of the total coliforms, while a removal efficiency of 77% was achieved in the case of fecal coliforms. No E. coli was detected as a result of implementing scheme IV. The combination of aeration and settling achieved significant reductions in turbidity, COD, and BOD5 with efficiencies of 83% and 66% for COD and BOD5 respectively. Significant reductions in levels of indicator organisms were not achieved till after the introduction of UV unit in scheme IV. As a result, 3-log removal was achieved in the case of the total coliforms, while a removal efficiency of 77% was achieved in the case of fecal coliforms. No E. coli was detected as a result of implementing scheme IV. Using the combination of 5-micron filtration and UV disinfection was not sufficient in achieving satisfactory results. Only with the aid of biological treatment, significant results were achieved.

Landscape plants (petunias and geraniums) irrigated with graywater did not show observable visual differences as compared to control plants irrigated with tap water. Plant tissue analysis results at the end of 7-month irrigation period demonstrated significant increase in the levels of sodium and total-N in the graywater-irrigated plants. Alternating irrigation using both tap water and graywater was successful in significantly reducing the accumulated amounts of sodium and total-N. Soil analysis results after 16 months of irrigation revealed that sodium and Sodium Adsorption Ratio (SAR) seemed to be the most affected by graywater irrigation.

The results of 511 surveys distributed to residents in the Gaza Strip revealed that about 84% of the interviewed people accepted the idea of using graywater. Knowing that installing a graywater system would cost the family about $500.00 reversed the acceptance rate of 84% to a rejection rate of about 90%. The situation returned back to the 84% acceptance rate when it was known that the cost paid by the resident would only be $50.00, with the rest of the cost to be contributed by an NGO. Surprisingly, the occupation of the interviewee and whether the house is connected or not to the sewer system did not affect the people's decision of whether or not to accept the use of graywater as demonstrated by the Chi-square tests.
Keywords: Gaza Strip; graywater; Palestine; wastewater reuse; civil engineering; environmental engineering